Negative Spontaneous Thoughts and Depression in Adolescents with Suicidal Ideation: Mediating Role of Cognitive Distortion and Cognitive Flexibility - Naderi, Hamaseh; Alizadeh, Shima; Alipour, Zeynab; Mahdizadeh Azdin, Somayeh; Khalilnezhad, Maryam (Shahroud Journal of Medical Sciences, 2024)
Background: This study aims to examine how cognitive distortion and cognitive flexibility contribute to the connection between negative spontaneous thoughts and depression among adolescents with thoughts of suicide. Methods: This study constitutes a descriptive-correlational and cross-sectional research design, utilizing Structural Equation Modeling (SEM) as the analytical approach. The target population for this research consists of all adolescents residing in Tehran from September to November 2023 who have previously attempted suicide. For this study, a sample of 214 adolescents with a history of suicide attempts was purposefully selected. The research instruments used in this study consisted of the BDI-II for measuring depression, the ICDS for assessing interpersonal cognitive distortions, the ATQ-30 for evaluating negative spontaneous thoughts, and the CFI questionnaire developed by Dennis and Vander Waal to measure cognitive flexibility. The research data was analyzed using the SPSS version 27 and SmartPLS version 4 software. The bootstrap method with a volume of 5000 was employed to examine the indirect relationships. In the same way, the significance of the mediator variable was examined using Sobel's test. Results: According to the findings, the helplessness component had a noticeable and adverse impact on the cognitive flexibility factor (β=-0.619, P<0.001). In addition, the cognitive flexibility variable was negatively and significantly influenced by the Individual incompatibility component (β=-0.225, P<0.001). Similarly, this particular component exhibited a significant effect on depression as well (β=0.159, p <0.001). Conclusion: The findings of the current research demonstrated the impact of cognitive flexibility and cognitive distortion on mitigating individual incompatibility, negative self-concept expectations, and depression among adolescents with suicidal ideation.